2017
DOI: 10.1111/pbi.12701
|View full text |Cite
|
Sign up to set email alerts
|

Spearmint R2R3‐MYB transcription factor MsMYB negatively regulates monoterpene production and suppresses the expression of geranyl diphosphate synthase large subunit (MsGPPS.LSU)

Abstract: SummaryMany aromatic plants, such as spearmint, produce valuable essential oils in specialized structures called peltate glandular trichomes (PGTs). Understanding the regulatory mechanisms behind the production of these important secondary metabolites will help design new approaches to engineer them. Here, we identified a PGT‐specific R2R3‐MYB gene, MsMYB, from comparative RNA‐Seq data of spearmint and functionally characterized it. Analysis of MsMYB‐RNAi transgenic lines showed increased levels of monoterpene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 103 publications
5
70
0
Order By: Relevance
“…Plants produce a large number of metabolites that are essential for ecological interactions and terpenes are natural products of the largest and structurally most diverse class ( Reddy et al., 2017 ). Terpenes play an important role in the communication between plants and the environment, between plants and animals, and between plants and plants; they can attract pollinators and seed spreaders, and they can act as defense agents against herbivores and pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Plants produce a large number of metabolites that are essential for ecological interactions and terpenes are natural products of the largest and structurally most diverse class ( Reddy et al., 2017 ). Terpenes play an important role in the communication between plants and the environment, between plants and animals, and between plants and plants; they can attract pollinators and seed spreaders, and they can act as defense agents against herbivores and pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PtMYB14 is a putative regulator of an isoprenoid-oriented response that contributes to the accumulation of sesquiterpene in conifers [49]. MsMYB combines with the promoter of geranyl diphosphate synthase and suppresses its activity to regulate monoterpene production negatively [24]. AtMYB21 and AtMYB24 contribute to the production of sesquiterpenes [42].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that SmMYB36 and SmMYB9b in salvia could positively regulate the biosynthesis of tanshinone [22,23]. Only MsMYB has been investigated to be a negative regulator of monoterpene biosynthesis by suppressing the expression of geranyl diphosphate synthase [24]. The roles of 2R-MYB genes and TFs in the terpenoid pathways of O. fragrans remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The members of this family extensively participated in terpenoids biosynthesis, not only in triterpenoids, but also other terpenoids. For example, spearmint (Mentha spicata) MsMYB binds to cis-elements of MsGPPS.LSU and suppresses monoterpene biosynthesis [35]. Artemisia annua AaMYB1 acts as activator in diterpene metabolism (artemisinin, AN) [36].…”
Section: Introductionmentioning
confidence: 99%